Single-cell profiling deciphering cholesterol metabolism dysregulation in metastatic uveal melanoma and implicating SLC45A2 in its prognosis - Zhou, Yiming; Cao, Yuan; Li, Zhaohui; Lei, Xinlan; Gao, Qiao; Yao, Wen; Guan, Jian; Lu, Guojing; Deng, Haiyu; Zhang, Lanyue; Deng, Xiaoxi; Chen, Zhen; et al. (Frontiers in Immunology, 2025)
IntroductionUveal melanoma (UM) is the most common primary intraocular malignancy in adults, characterized by high metastatic potential, primarily to the liver. UM exhibits unique molecular drivers, such as GNAQ/GNA11 mutations, and a distinct immune microenvironment. Despite these insights, the correlation and underlying mechanisms of lipid and cholesterol metabolism in UM development and progression have been scarcely investigated.MethodsSingle-cell data analysis and cellular communication analysis were employed to investigate the effect of cholesterol metabolism in UM and its relationship with cell-cell communication and tumor immunology. Single-cell data of UM were acquired from the GEO repository and analyzed using R software. Key genes associated with cholesterol metabolism were validated in vitro using the human metastatic uveal melanoma cell line C918 and MuM2B.ResultsSingle-cell analysis revealed cellular heterogeneity in primary and metastatic UM samples. Metastatic UM tumor cells exhibited significantly lower cholesterol metabolism scores compared to primary tumor cells. Cell-cell communication analysis indicated that the Cho-high group demonstrated significantly higher levels of communication number and intensity. The APP-CD74 pathway was found to have relatively higher outgoing ligand-receptor communication in the Cho-high group. GSEA analysis found the mTORC1 signaling pathway and oxidative phosphorylation pathway is correlated to the cholesterol metabolism scores in melanoma cells in the UM dataset. Through correlation analysis and Cox regression, the gene SLC45A2 was identified as correlated with overall survival in both the TCGA-UVM dataset and the GSE84976. In vitro experiments showed that SLC45A2 depletion attenuated the metastatic and proliferative capacities of uveal melanoma cells.ConclusionOverall, this study provides the first single-cell level investigation of cholesterol metabolism in UM and identifies SLC45A2 as a potential key gene affecting UM progression by regulating cholesterol metabolism. These findings offer new perspectives on the role of cholesterol metabolism in UM and lay a foundation for future clinical applications.